ROLE OF ECTOPIC PROLACTIN ON THYROID HORMONES LEVEL IN A SAMPLE OF IRAQI INFERTILE WOMEN WITH UTERINE FIBROIDS (Iraqi Journal of Medical Sciences, 2016)
Background:A large number of traditional investigations and bioassay of hormones have been practiced in the diagnosis and management of infertility for a long time. Measurements of prolactin and thyroid stimulating hormone have been considered important components of the evaluation of women presenting with infertility.Objectives:To study the effect of prolactin hormone produced from uterine fibroid(s) on thyroid hormones levels and role of these hormones.Methods: One hundred three women with uterine fibroid were entered to the Obstetrics and Gynecology Department in Al-Kadhimyia Teaching Hospital in Baghdad-Iraq from the 15th of June 2007 to December 30th 2010. Fasting serum prolactin, total T3, total T4, and thyroid stimulating hormone (TSH) were estimated using MiniVIDAS [ELFA (Enzyme Linked Fluorescent Assay)] kits.Results:Forty five out of 103 (43.69%) women were found with primary infertility and the rest 58 (56.31%) with secondary infertility. Serum thyroid hormones mean ± standard deviations were found normal before and after surgery in both primary and secondary infertile women. Level of serum prolactin was found elevated about 9 folds in primary infertile women and 8 folds in those with secondry infertility before surgery more than their levels after. No significant difference was found between thyroid hormones before and after surgery in both infertile groups, unlike their prolactin which was found highly significant with p value
Keywords: Infertility; Ectopic prolactin; Thyroid hormones; Uterine fibroids